The Effect Of Person Organization Fit And Job Embeddingness On Organizational Citizenship Behavior At PLN - Endri Haryati; Teguh Setiawan Wibowo; Agus Purbo Widodo (CV. AFDIFAL MAJU BERKAH, 2025)
Person–organization fit is commonly understood as the degree to which an organization’s values align with those held by individuals. This alignment is shaped not only by shared values, but also by similarities in personality and compatibility with colleagues. On the other hand, job embeddedness represents a comprehensive collection of factors that determine whether an employee remains in a role or decides to leave. Researchers typically evaluate this construct across three interrelated dimensions: fit, link, and sacrifice. Organizational Citizenship Behavior (OCB) belongs to the broader field of organizational behavior, focusing on discretionary actions that are neither explicitly defined nor formally rewarded. One way to view OCB sees it as extra-role performance—activities that fall outside the boundaries of the job description. Alternatively, it can be seen through a political or philosophical lens, framing OCB as akin to citizenship within an organization. In both interpretations, OCB reflects an employee’s personal convictions or perceptions of an unwritten psychological contract with the organization, motivating them to contribute beyond their formal duties.In this study, OCB is measured using a multifaceted set of indicators, including helping behavior, organizational compliance, sportsmanship, loyalty, individual initiative, social quality, and self-development. To explore how person–organization fit and job embeddedness influence OCB, we employed PLS (Partial Least Squares) path modeling using SmartPLS 3.0, yielding a comprehensive path diagram of the interrelationships among these variables. Our validity analysis revealed that all indicators for person–organization fit, job embeddedness, and OCB achieved factor loadings above 0.7, confirming their relevance in measuring each respective construct. Additionally, convergent validity was supported by AVE values exceeding 0.5 for all variables. Reliability assessments showed Cronbach’s Alpha scores above 0.6 and Composite Reliability values above 0.7, indicating stable and consistent measurement frameworks.Structural model results indicated that person–organization fit and job embeddedness together explained 15.3% of the variance in OCB (R² = 0.153), suggesting that the majority of variance is accounted for by other factors. Nevertheless, hypothesis testing confirmed that both person–organization fit and job embeddedness significantly influence OCB among PLN employees (p < 0.05), underscoring their important—but partial—role in predicting extra-role, citizenship behavior in organizational settings.